An In Vitro Comparison ofApical Leakage of Biocalex, White MTA, Gray MTA, and Amalgam as Root-End Fillings - P. Ghaziani; Gh. Sadeghi (Tehran University of Medical Sciences, 2008)
Objective: In a cavity prepared through endodontic surgery, application of a material to provide apical seal and prevent bacterial and tissue exudates is of great importance. The purpose of this study was to compare the sealing ability of Biocalex with white MTA, gray MTA, and amalgam as root-end fillings. Materials and Methods: Sixty-six single-rooted extracted human teeth were cleaned, shaped, and obturated with gutta-percha. The root apices were resected and 3 mm deep retrograde cavity was prepared. The teeth were assigned randomly into four groups of 15 teeth each and retrofilled with Biocalex, gray MTA, white MTA, and amalgam. Six teeth served as positive and negative controls. All root surfaces, except the ending part, were covered with two layers of nail polish. The roots were then stored in 2% methylene blue for 72 hours and embedded in polyester resin. The teeth were sectioned buccolingually and maximum extent of dye penetration was evaluated through a stereomicroscope. Statis-tical analysis was carried out by one way ANOVA and Tukey test. Results: Biocalex showed significantly less leakage compared to the other three materials P<0.05. White MTA showed significantly lower amount of leakage as Compared to gray MTA and amalgam P<0.05. Conclusion: The findings of this study showed that retrograde filling with Biocalex can achieve proper sealing ability and this material can be used as an alternative for MTA and amalgam.